Desired points at minimum cost in the “Optimize Energy Performance” credit of leed certification - Akcay, Emre Caner; Arditi, David (Journal of Civil Engineering and Management, 2017)
This paper presents a method that guides designers in obtaining the desired number of earned points in the “Optimize Energy Performance” credit of the “Energy and Atmosphere” category of LEED version 4 (v4) certification at minimum cost. The model creates different scenarios, identifies the LEED points and  costs for each scenario. The energy analysis calculations are performed by Sefaira, the quantities of materials are received from Autodesk Revit, and the cost information comes from the RSMeans Database. A macro in Excel automates the process. An office building was used as a case study to illustrate the applicability of the proposed method. The minimum cost necessary to achieve any number of points in the “Optimize Energy Performance” credit were calculated, such as a minimum cost of $842,500 to obtain 16 points, and $476,684 for 5 points. The primary contributions of this research include (1) the development of a tool that allows designers to pick the most economical alternative for the desired points in the “Optimize Energy Performance” credit, and (2) the first time integrated use of an energy simulation software (Sefaira), a cost database (RSMeans), and a BIM software (Autodesk Revit).